2017
DOI: 10.5152/tud.2016.98958
|View full text |Cite
|
Sign up to set email alerts
|

Top cited articles in urology from Turkey

Abstract: Objective: Citation is the name given for a scientific publication in order to be used as a reference by another publication. In this study, we reviewed the most frequently cited publications in urology from Turkey. Although the number of citations is not completely definitive on its own, it shows the importance and effect of the publication. Besides the number of citations directly determines the impact factor of the journals and this factor is generally used in the evaluation of the quality and importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Hovewer, the common emphasis of the last two studies is renal transplantation. Unlike previous bibliometric researches, Ipekci et al [25] showed that the most cited publications in Turkey belonged to urolithiasis (23.5%) and andrology areas (infertility: 15.6% and sexual dysfunction: 11.7%) in their country-based research. In another study Thomas et al [15] suggested that the most cited papers or classic papers in urology varied depending on the time period studied.…”
Section: Aetiologic/therapeuticmentioning
confidence: 77%
See 1 more Smart Citation
“…Hovewer, the common emphasis of the last two studies is renal transplantation. Unlike previous bibliometric researches, Ipekci et al [25] showed that the most cited publications in Turkey belonged to urolithiasis (23.5%) and andrology areas (infertility: 15.6% and sexual dysfunction: 11.7%) in their country-based research. In another study Thomas et al [15] suggested that the most cited papers or classic papers in urology varied depending on the time period studied.…”
Section: Aetiologic/therapeuticmentioning
confidence: 77%
“…Recently, local or country-specific bibliometric analysis have been also reported. [25] Even though there are many publications on urological emergencies in current literature, there are very few bibliometric studies. [26] In this study, we conducted the bibliometric analysis of top 100 cited articles on urological emergencies since 1975 among 360 articles we obtained by using [27] We determined that the most cited article (467-fold cited) was "International Clinical Practice Guidelines for the Treatment of Acute Uncomplicated Cystitis and Pyelonephritis in Women: A 2010 Update by the Infectious Diseases Society of America and the European Society for Microbiology and Infectious Diseases" by Gupta et al [28] Citation numbers and being published in journals with high impact factors are important indicators of the quality of an article.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of top-cited articles has been used in different fields, including cancer immunotherapy (Zhang et al, 2019a), cardiology (Shuaib et al, 2015), gastroenterology and hepatology (Azer and Azer, 2016), and urology (Ipekci et al, 2017). However, there is no top-cited analysis of the comorbidity of pain and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Citation number of one article is commonly used to assess the academic influence of the study. Bibliometric analysis is frequently used to evaluate the academic developments of specific specialties, including cancer, [6,7] neuroscience, [8] urology, [9] emergency medicine [10] and medical imaging. [11] In recent years, bibliometric analysis becomes increasing popular in orthopedics, which mainly focus on spinal cord tumors, [12] anterior cruciate ligament injuries, [13] back pain, [14] orthopaedic surgeries, [15] knee research [16] , and hand surgeries.…”
Section: Introductionmentioning
confidence: 99%